ADVERTISING CAMPAIGN MANAGEMENT IN THE VIDEO PRODUCTION MARKET - Solntsev, Sergii O.; Solovyov, Oleksandr O. (Journal of Strategic Economic Research, 2026)
The article is dedicated to the study of the principles, structure, and mechanisms of managing advertising campaigns in the video production market, which operates at the intersection of creative, technological, and communication-management processes. In the current conditions of digital transformation and the rapid growth of visual content consumption, video production is becoming not only a technical process of creating audiovisual materials but also a strategic tool for shaping brand perception, emotional engagement, and long-term competitive advantages for companies. This underscores the need to shift from traditional advertising approaches to integrated management systems that combine analytical research, creative design, and technological innovation. The article examines the theoretical foundations of video production as both a service and a product, highlighting its dual role in shaping communicative and reputational value. It is shown that the effectiveness of an advertising campaign in this sector depends on the coherence of concept development, creative dramaturgy, production and post-production stages, as well as the alignment of these elements with strategic marketing objectives. The main models of interaction between the client, the production company, and the media agency are analyzed, defining the distribution of responsibilities, decision-making logic, and risk sharing. The article emphasizes the importance of integrating creative identity, technological capabilities, and strategic planning to achieve maximum communication effectiveness. It substantiates the approach where video content serves not only as a carrier of information but also as a demonstration of the company’s professional style and expertise. Special attention is given to the determinants influencing the choice of communication tools - market, sociocultural, technological, behavioral, creative, and innovative - which shape the adaptability and competitiveness of advertising campaigns in the video production market.